PRINSIP UMUM PENATALAKSANAAN CEDERA OLAHRAGA HEAT STROKE - Ade Tobing, Saharun Iso, (Jorpres (Jurnal Olahraga Prestasi), 2016)
ABSTRACT Exercises that are conducted in an extreme heat environment can cause heat injury. Heat injury is associated with disturbance to temperature regulation and cardiovascular systems. Heat stroke is the most severe type of heat injury. Heat stroke is associated with high morbidity and mortality numbers, particularly if therapy treatment is delayed. In general, heat stroke is caused by two things, namely increase in heat production and decrease in heat loss. Heat stroke signs include: (1) rectal temperature above 40.5°C; (2) hypotension, tachycardia, tachypnea; (3) changes in mental status (e.g. irritability, ataxia, confusion, disorientation, syncope, hysteria, and coma); (4) reduced ability to lower body temperature (e.g. stop sweating and skin becoming hot); (5) signs of a life-threatening: disseminated intravascular coagulant or DIC (e.g. epistaxis, bleeding from intravenous line, bruises, and pulmonary edema) and signs of Acute Renal Failure or ARF (e.g. peripheral edema). Symptoms of heat stroke include fatigue, headache, nausea, and vomiting. Management of heat stroke injuries is by continuously performing cooling down as quickly as possible while resuscitating patient. Intensive care must be carefully considered to the respiratory tract, reducing body temperature, limiting the production of heat, optimizing air circulation and monitoring and treating complications. Quick decrease in body temperature is the most important things in treatment. Keywords: Heat injury, heat stroke ABSTRAK Latihan yang dilakukan di lingkungan panas yang ekstrim dapat menyebabkan terjadinya cedera panas. Cedera panas berhubungan dengan gangguan terhadap sistem pengaturan suhu dan sistem kardiovaskuler. Heat stroke merupakan bentuk yang paling parah dari cedera panas. Heat stroke berhubungan dengan angka morbidilitas dan mortalitas yang tinggi terutama jika penanganan terapinya terlambat. Penyebab heat stroke secara umum diakibatkan oleh dua hal, yaitu: peningkatan produksi panas, dan penurunan kehilangan panas. Tanda- tanda Heat stroke meliputi: (1) Suhu dubur di atas 40.5°C; (2) Hipotensi, tachycardia, tachypnea;(3) Perubahan status mental (irritability, ataxia, confusion, disorientasi, syncope, hysteria, dan koma); (4) Berkurangnya kemampuan untuk menurunkan suhu tubuh (berhenti bekeringat, kulit menjadi panas); (5) Tanda-tanda yang mengancam jiwa: disseminated intravascular coagulant (DIC), termasuk epistaxis, pendarahan dari saluran intra vena ,luka memar, dan edema paru, tanda dari Acute Renal Failure (ARF), termasuk edema periperal. Gejala heat stroke meliputi: kelelahan, pusing, mual, dan muntah. Penatalaksanaan cedera heat stroke yaitu dengan melakukan pendinginan secepat mungkin dan terus menerus sambil pasien disadarkan. Perawatan intensif harus diperhatikan dengan cermat untuk saluran pernapasan, mengurangi suhu tubuh, membatasi produksi panas, mengoptimalkan sirkulasi udara dan memonitor serta mengobati komplikasi. Penurunan suhu tubuh dengan cepat merupakan hal yang terpenting dalam perawatan. Kata kunci: Cedera panas, heat stroke